Antianaerobe Activity of RBX 7644 (Ranbezolid), a New Oxazolidinone, Compared with Those of Eight Other Agents - Ednie, Lois M. (American Society for Microbiology, 2003)
The activity of ranbezolid (RBX 7644), a new oxazolidinone, against 306 anaerobes was compared with those of 11 other agents. The MICs at which 50% of the isolates tested are inhibited and those at which 90% of the isolates tested are inhibited (in micrograms per milliliter) were as follows: ranbezolid, 0.03 and 0.5; linezolid, 2 and 4; vancomycin, >16 and >16; teicoplanin, 1 and >16; quinupristin-dalfopristin, 1 and >8; amoxicillin-clavulanate, 0.5 and 2; imipenem, 0.125 and 1; clindamycin, 0.25 and 8; metronidazole, 1 and 4; gatifloxacin, 0.5 and 4; and moxifloxacin, 0.5 and 2, respectively. Ranbezolid had very good in vitro activity against both gram-negative and -positive anaerobes.